Autocatalytic sludge pyrolysis by biochar derived from pharmaceutical sludge for biogas upgrading. (15th August 2021) - Liu, Huidong; Xu, Guoren; Li, Guibai
Abstract: As a solid waste rich in organic matter, pharmaceutical sludge can be effectively treated by pyrolysis and converted into energy. In this study, biochar prepared from pharmaceutical sludge was used for autocatalytic pyrolysis so as to improve the yield and quality of biogas while reducing the production of bio-oil. The results showed that biochar produced by pyrolysis from pharmaceutical sludge has high specific surface area and abundant functional groups. The addition of catalyst reduced the yield of bio-oil and increased the content of aromatics in bio-oil. At the same time, the yield of biogas was improved. When the catalyst was added to 60% at 800 °C, the combustible component in biogas reached 72.93% and the HHV reached 13.23 MJ/m 3 . Through calcination and deashing treatment of pharmaceutical sludge biochar, the roles of ash and deashing biochar in the autocatalytic process were analyzed. The results showed that ash was the active component of autocatalysis, and carbon was involved in the reaction as a reactant. Meanwhile, the porous structure of biochar increased the active sites. The experiment results showed that autocatalysis process can produce clean energy while treating pharmaceutical sludge, which has guiding significance for the industrial application of treating sludge produced by pharmaceutical enterprises. Graphical abstract: Image 1 Highlights: The characteristics of biochar derived from pharmaceutical sludge were analyzed. The addition of catalyst reduced the yield of bio-oil and increased the content of aromatics in bio-oil. The experiment results showed that autocatalysis process can produce clean energy while treating pharmaceutical sludge.